2008
DOI: 10.1542/peds.2007-2657
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal Infection and Exacerbations of Childhood Tics and Obsessive-Compulsive Symptoms: A Prospective Blinded Cohort Study

Abstract: Patients who fit published criteria for pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections seem to represent a subgroup of those with chronic tic disorders and obsessive-compulsive disorder who may be vulnerable to group A beta-hemolytic streptococcus infection as a precipitant of neuropsychiatric symptom exacerbations. Group A beta-hemolytic streptococcus infection is not the only or even the most common antecedent event associated with exacerbations for these patients. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
109
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(128 citation statements)
references
References 38 publications
12
109
1
2
Order By: Relevance
“…Although the investigators in both studies prospectively identified PANDAS cases based on the published criteria, only a small minority of the clinical exacerbations recorded were consistent with the descriptions of PANDAS exacerbations in which the period of increased tic or OC symptom severity is associated with a sudden increase in the severity of psychiatric comorbidity, including emotional lability, intense anxiety, cognitive deficits, oppositional behaviors, motoric hyperactivity, and/or dysgraphia (Swedo et al 1998). Although studies have linked antecedent GAS infections to symptom exacerbations, the majority occur without evidence of antecedent infection, suggesting that GAS infection may not be the only agent responsible for exacerbations (Kurlan et al 2008), which has also been reported for SC (Berrios et al 1985). The reasons for this discrepancy are not clear, but suggest that the PANDAS cases identified by these studies may not be the same as the PANDAS cases studied by Swedo and colleagues.…”
Section: Serologic and Prospective Studiessupporting
confidence: 84%
See 3 more Smart Citations
“…Although the investigators in both studies prospectively identified PANDAS cases based on the published criteria, only a small minority of the clinical exacerbations recorded were consistent with the descriptions of PANDAS exacerbations in which the period of increased tic or OC symptom severity is associated with a sudden increase in the severity of psychiatric comorbidity, including emotional lability, intense anxiety, cognitive deficits, oppositional behaviors, motoric hyperactivity, and/or dysgraphia (Swedo et al 1998). Although studies have linked antecedent GAS infections to symptom exacerbations, the majority occur without evidence of antecedent infection, suggesting that GAS infection may not be the only agent responsible for exacerbations (Kurlan et al 2008), which has also been reported for SC (Berrios et al 1985). The reasons for this discrepancy are not clear, but suggest that the PANDAS cases identified by these studies may not be the same as the PANDAS cases studied by Swedo and colleagues.…”
Section: Serologic and Prospective Studiessupporting
confidence: 84%
“…Neither of these studies provides a strong support for the PANDAS hypothesis (Kurlan et al 2008;Leckman et al, in submission). Kurlan et al (2008) reported the results of a prospective, multicenter study of children who met stringent criteria for PANDAS (n ¼ 40) and matched children with OCD or tic disorders (n ¼ 40) who completed monthly throat cultures, 3-month blood antibody tests, and monthly phone or in-clinic evaluations for an average of 2 years (Kurlan et al 2008). Although they did find a significantly higher rate of GAS infections as well as a higher rate of clinical exacerbations among the PANDAS cases, no more than 25% of the exacerbations in the PANDAS cases were temporally associated with a GAS infection.…”
Section: Serologic and Prospective Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…Ever since, several studies tried to prove this hypothesis, and a pathophysiological model was created to explain how a possible immunological effect could regulate dopaminergic circuitry leading to tics, but no definitive proof could be elicited. Nevertheless, no study has ever confirmed that a previous history of infection due to beta-hemolytic streptococci was associated with the onset or exacerbation of tics or OCD 9 .…”
Section: The Immunological Hypothesis and Pandasmentioning
confidence: 99%